First record of the broad-banded cardinal fish Apogon fasciatus (White, 1790) from Turkey - TURAN, C.; YAGLIOGLU, D.; ERGUDEN, D.; GURLEK, M.; SONMEZ, B. (Mediterranean Marine Science, 2010)
Two specimens of the alien cardinal fish Apogon fasciatus (White, 1790) are recorded for the first time from Turkey and second time from the Mediterranean Sea. This is the fourth Indo-Pacific apogonid species documented in the Mediterranean Sea, and the introduction of this species to the eastern Mediterranean is due to migration from the Red Sea via the Suez Canal.